EXPLORING TRANSLANGUAGING PRACTICES IN PODCAST THE INDAH G SHOW - Mai, Menghuan; Nurhayani, Ika; Rusmawati, Roosi (Brawijaya University Library, 2024)
This research investigates translanguaging dynamics in the context of podcasts, focusing on the alternation between English and Indonesian languages. The study aims to uncover patterns, functions, and implications of language alternation in this digital communication medium. Employing a qualitative approach, podcast episodes are transcribed, translated, and analyzed to identify instances of translanguaging. The findings provide insights into the complex interplay of linguistic elements in podcast discourse and contribute to the understanding of sociolinguistic practices in the digital age.